2023
DOI: 10.1038/s41588-023-01399-7
|View full text |Cite
|
Sign up to set email alerts
|

Triplication of the interferon receptor locus contributes to hallmarks of Down syndrome in a mouse model

Abstract: Down syndrome (DS), the genetic condition caused by trisomy 21, is characterized by variable cognitive impairment, immune dysregulation, dysmorphogenesis and increased prevalence of diverse co-occurring conditions. The mechanisms by which trisomy 21 causes these effects remain largely unknown. We demonstrate that triplication of the interferon receptor (IFNR) gene cluster on chromosome 21 is necessary for multiple phenotypes in a mouse model of DS. Whole-blood transcriptome analysis demonstrated that IFNR over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 113 publications
(182 reference statements)
2
31
0
Order By: Relevance
“…( Figure 5 D). This result is consistent with the triplication of Ifnar1 , Ifnar2 , and Ifngr2 in the Dp16;ACE2 mice [ 27 ] and indicates that mice with Down syndrome have a hyperactive IFN-I response during acute SARS-CoV-2 infection.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…( Figure 5 D). This result is consistent with the triplication of Ifnar1 , Ifnar2 , and Ifngr2 in the Dp16;ACE2 mice [ 27 ] and indicates that mice with Down syndrome have a hyperactive IFN-I response during acute SARS-CoV-2 infection.…”
Section: Resultssupporting
confidence: 84%
“…Because many social and behavioral factors, such as maintaining distance from others and wearing masks, can greatly alter SARS-CoV-2 transmission and the outcome of COVID-19, to better understand COVID-19 pathogenesis it is critical that experimental infection be conducted to ensure that all conditions are under control. We chose to model SARS-CoV-2 infection in the Dp(16)1Yey/+ mouse mutant line, which is triplicated for the entire human chromosome 21 syntenic region on mouse chromosome 16 and currently the most widely used mouse model of Down syndrome [ 14 , 23 , 24 , 25 , 26 , 27 ]. At the time the study commenced, it was reported in a preprint that a transgenic mouse model that expresses human ACE2 receptor (K18-hACE2) was susceptible to SARS-CoV-2 infection that resulted in severe lung inflammation and impaired function [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the INCLUDE (INvestigation of Co‐occurring conditions across the Lifespan to Understand Down syndromE) program at NIH has ushered in a renaissance of new investigators, new ideas, and increased funding with the goal of helping persons with DS live longer and healthier lives. For example, trisomy 21 and the Dp16 mouse of DS have been associated with consistent activation of interferon responses 11,31 . Despite insights gained from studies on congenital abnormalities of airways and on immune cell defects, there are unfortunately few studies yet available that illuminate why people with DS are so susceptible to severe, lethal, and recurrent respiratory tract infection.…”
Section: Discussionmentioning
confidence: 99%